Mesoporous Co3O4/In2O3 nanocomposites for formaldehyde gas sensors: Synthesis from ZIF-67 and gas-sensing behavior. (August 2023) - Guo, W.Q.; Niu, J.Y.; Hong, B.; Xu, J.C.; Han, Y.B.; Peng, X.L.; Ge, H.L.; Li, J.; Zeng, Y.X.; Wang, X.Q.
Highlights: Mesoporous In2 O3 NWs are prepared with nanocasting method using SBA-15. In2 O3 /Co3 O4 nanocomposites are synthesized from mesoporous ZIF-67 MOFs. Co3 O4 nanoparticles greatly affect the microstructures and gas-sensing properties. P-type Co3 O4 decreases the operating temperature owing to the catalysis. Oxygen vacancies play a dominant role to improve the gas-sensing performance. Abstract: Mesoporous In2 O3 nanowires (NWs) were synthesized with nanocasting method, and then Co3 O4 /In2 O3 nanocomposites were prepared through calcining ZIF-67. All results indicate that Co3 O4 nanoparticles greatly affect the microstructures and gas-sensing properties of Co3 O4 /In2 O3 sensors. The response to 10 ppm (formaldehyde) HCHO gas exhibits a significant improvement though the loading of Co3 O4 . The response values soar from 26.16 for In2 O3 NWs to 92.94 for 6%Co3 O4 /In2 O3 and up to maximum 113.6 for 8% Co3 O4 /In2 O3, then decreases to 25.76 for 10% Co3 O4 /In2 O3 . 8% Co3 O4 /In2 O3 sensor possesses the excellent HCHO gas-sensing performance with the highest response (113.6) and shortest response time of 20 s. The working temperature of Co3 O4 /In2 O3 sensors is 30 °C lower than that of In2 O3 sensor due to Co3 O4 catalysis. P-n heterojunctions between p-type Co3 O4 and n-type In2 O3 affect the interfacial carrier distribution, improving the gas-sensing behavior of Co3 O4 /In2 O3 sensors. Furthermore, oxygen vacancies also play a important role to improve the gas-sensing performance of Co3 O4 /In2 O3 sensors. Graphical abstract: Image, graphical abstract